Prognostic significance of head and neck spindle cell carcinoma. Issue 3 (30th December 2022) - Patel, Aman M.; Choudhry, Hannaan S.; Desai, Amar D.; Shah, Vraj P.; Patel, Prayag; Eloy, Jean Anderson; Roden, Dylan F.; Fang, Christina H.
Abstract: Background: Our study investigates the prognostic significance of spindle cell histology on overall survival (OS) of conventional head and neck squamous cell carcinoma (HNSCC). Methods: The 2004 to 2017 National Cancer Database was queried for patients with head and neck spindle cell carcinoma (HNSpCC) (n = 1572) or HNSCC (n = 242 697) of the oral cavity, major salivary glands, sinonasal tract, oropharynx, hypopharynx, and larynx treated with curative intent. Results: Patients with HNSpCC presented more frequently with higher‐grade tumors and cN0 disease than those with HNSCC ( p <  0.001). In the oral cavity, the HR for death for SpCC compared with SCC was 1.33 ( p <  0.001). In the oropharynx, the HR for death for SpCC compared with SCC was 1.47 ( p  = 0.028). Conclusions: After adjusting for patient, tumor, and treatment characteristics, SpCC histology had an independent adverse prognostic effect on OS in the oral cavity and oropharynx. SpCC histology does not necessarily portend poorer survival in all HNSCC. Level of Evidence: 4.